Tecendo rupturas: o processo da recriação televisual de Dom Casmurro - Coca, Adriana Pierre (2013)
The purpose of the research is to discuss processes break with the classical language of televisual narrative fictional recreation of the novel Don Casmurro, which is the micro-series Capitu (2008) TV Globo, under the relations chronotopic and intermediality. The hypothesis that arises is that Capitu renews in how languages mix and subverts spacetime. The methodology adopted is transmethodology (MALDONADO, 2011), which runs through three dimensions: the contextualization of the object , the empirical research and theoretical. The theoretical basilar consists mainly of the concepts of chronotope and carnivalization Mikhail M. Bakhtin and the Theory of intermediality (GLÜVER, 2006), which allows to observe the different art forms established in a given text, conceptually merged. The reflection begins with a discussion of the contemporary televisual language and context of the new logic imposed by the current context of media convergence. Important information to understand why production was possible with the features listed Capitu. The research progresses with exposure matrices as a basis for the construction of narrative fiction on TV, at the continuities are presented adhering to language conventional television, which are maintained in micro-series. Then , the analysis and interpretation of scenes , which constitute the empirical research relating the texts that related how it operates subversion of chronotope (GATTI, 2012) and at what times is observed carnivalization, steps on the breaks observed are placed on the table. The work matters to Communication Sciences, since television is the main vehicle of mass communication in Brazil and fiction occupies a significant space in the programming of the stations open. We conclude that Capitu is a intermidiality product that brings out the reconfiguration of new ways to produce and narrate on TV, presenting an ambiguity diegetic, which puts the viewer in touch with a text unsettling and can lead to reflection.